Evaluating the test–retest reliability of symptom indices associated with the ImPACT post-concussion symptom scale (PCSS). Issue 4 (21st April 2018) - Merritt, Victoria C.; Bradson, Megan L.; Meyer, Jessica E.; Arnett, Peter A.
ABSTRACT: Objective : The Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) is a commonly used tool in sports concussion assessment. While test–retest reliabilities have been established for the ImPACT cognitive composites, few studies have evaluated the psychometric properties of the ImPACT's Post-Concussion Symptom Scale (PCSS). The purpose of this study was to establish the test–retest reliability of symptom indices associated with the PCSS. Participants and Methods : Participants included 38 undergraduate students (50.0% male) who underwent neuropsychological testing as part of their participation in their psychology department's research subject pool. The majority of the participants were Caucasian (94.7%) and had no history of concussion (73.7%). All participants completed the ImPACT at two time points, approximately 6 weeks apart. The PCSS was the main outcome measure, and eight symptom indices were calculated (a total symptom score, three symptom summary indices, and four symptom clusters). Results : Pearson correlations ( r ) and intraclass correlation coefficients (ICCs) were computed as measures of test–retest reliability. Overall, reliabilities ranged from low to high ( r = .44 to .80; ICC = .44 to .77). The cognitive symptom cluster exhibited the highest test–retest reliability ( r = .80, ICC = .77), followed by the positive symptom total (PST) index, an indicator of the total number of symptoms endorsed ( r = .71, ICC = .69). In contrast, the commonly used total symptom score showed lower test–retest reliability ( r = .67, ICC = .62). Paired-samples t tests revealed no significant differences between test and retest for any of the symptom variables (all p > .01). Finally, reliable change indices (RCI) were computed to determine whether differences observed between test and retest represented clinically significant change. RCI values were provided for each symptom index at the 80%, 90%, and 95% confidence intervals. Conclusion : These results suggest that evaluating additional symptom indices beyond the total symptom score from the PCSS is beneficial. Findings from this study can be applied to athlete samples to assess reliable change in symptoms following concussion.